مدى تحقيق أدوات التمويل الخضراء التنمية المستدامة = Scope of green financing instruments to achieve sustainable development - Negasi, Mohamed Ibrahim; Laeba, Muhammad; Zaki, Hisham Mahmud (IIUM Press, International Islamic University Malaysia, 2019)
تقومهذه الدراسة بمعالجة موضوع تحقيق أدوات التمويل الخضراءالتنمية المستدامة، حيث تناولتبيان معنى السندات والصكوك الخضراء وخطوات إصدارها، و أبعادها وخصائصها، ث تعرضت الدراسة لبيان الحكم الشرعي للسندات والصكوك الخضراء، كما ناقشت مدى إمكانيتهما لتحقيق التنمية المستدامة للمجتمع. استخدمت الدراسة المنهج الاستقرائي لتتبع آراء الباحثين حول الموضوع،متامكاستخدام المنهج التحليلي لتحليل تلك الآراء.وقد توصلت الدراسة إلى جملة من النتائج أهمها: عدم جواز التعامل بالسندات الخضراء؛لأنها تقوم على الربا، وبالنسبة للصكوك الخضراء فإنها لا تجوزأيضا؛لأن فيها شبهة الربا،ةيسملااةميقلبادترسُتانهوكل، وأن هذه الأدوات اهنمعقوتُيناكامكةيلاعتاجردبةمادتسلماةيمنتلاققتحلاةيليومتلا ***************************************************************************** This paper addresses the issue of achieving sustainable development through green financing instruments, where it discusses the meaning of green bonds and Sukuk, the steps of their issuance, their dimensions, and characteristics. The paper also examines the provision of Shariah on green bonds and Sukuk and discusses the extent of their capability to achieve sustainable development of society. This study uses the inductive approach to track the opinions of researchers on the subject as well as the analytical approach to analyze those opinions. The study has reached a number of conclusions, the most important of which are: the impermissibility of dealing with green bonds because they are based on riba. Likewise, green Sukuk is also not permissible in Shariah because of the suspicion of riba in it, as it is recovered at nominal value, and these financing instruments do not contribute to the achievement of sustainable development to the highest degree as expected.